The adaptation of Nujum Pa Blalang (1959) as virtual game elements / Nadhirah Ishak - Ishak, Nadhirah (2019)
The aim of this research is to adapt the film Nujum Pa’ Blalang (1959) as a virtual game content. In many years, there are many games adapted from film. Derived from local folklore, the film director, P. Ramlee, adapted the local folklore into the film Nujum Pa' Blalang. The film Nujum Pa' Blalang has been awarded both internationally and locally. This research applies a qualitative approach. Two questionnaires were distributed to respondents between 19-25 years old to discover their preference based on the highest five selection scenes of film Nujum Pa’ Blalang as the foundation of the study. The study uses a template developed by Järvinen (2008) as an instrument to analyse game elements and propose the use of game mechanics based on the top five scenes chosen by the respondents towards the film Nujum Pa' Blalang. The research has discovered the game elements and has formulated the model of the game mechanics based on the five scenes of film Nujum Pa’ Blalang. This research hopes to contribute in assisting during the critical process of pre-producing games in adapting films to games. The findings of this study will contribute in providing methods in finding the virtual game elements based of films derived from local culture, as it will be beneficial to the local heritage and the development of Malaysia’s creative industry.